Cognitive and Informational Foundations of Kazakh Scientific Terminology (Based on K. Satpayev’s “Algebra” Textbook) (Eurasian Journal of Philology Science and Education, 2025)
The article provides a comprehensive examination of the cognitive and informational foundations of Kazakh scientific terminology based on the materials of Kanysh Satbayev’s textbook Algebra. The relevance of the study lies in viewing the term not only as a nominative unit but also as a cognitive structure that functions as a repository of information and an organizer of scientific knowledge. The terminological system is described as a semiotic and informational model that reflects the interrelation between national worldview and scientific cognition. The main objective of the research is to determine the cognitive and informational nature of the term and to identify the mechanisms of conceptual system development and the accumulation of terminological information in the Kazakh scientific language. The study employs methods of cognitive analysis, linguocultural and definitional approaches, semantic modeling, and comparative-typological techniques.The findings demonstrate that the terms created by K. Satbayev embody models of collective scientific memory and that their internal form reflects scientific information and elements of national experience. The cumulative and dynamic nature of terminological information is revealed, along with the mechanisms of forming a new terminological system. Furthermore, the study highlights the conceptual role of Satbayev’s terminology in the evolution of the Kazakh scientific style and clarifies its significance in structuring the modern terminological corpus. The results provide a methodological basis for constructing a cognitive map of Kazakh scientific discourse and enhancing domain-specific terminological development processes. The research outcomes may be applied in courses on cognitive linguistics, terminology studies, and the history of scientific language, as well as in the teaching practice of Kazakh scientific terminology.Keywords: cognitive linguistics, terminology, information, K. Satbayev, Algebra.